Masculine brave in the feminine winter sports - Béki, Piroska (Applied Studies in Agribusiness and Commerce, 2015)
The sport has significant role in the changes of the genders relation and helped to transform the conception of the sexes during the last fifty years. The women started to do conventionally male sports; the newest event was the ski jumping for female athletes at the Olympic Games of Soci. The gender stereotypes in the women sports can be stronger or weaker depending on the success or on the water haul. This phenomenon helps us to understand the new conceptions of the sexes in the context of the relationships of genders.